Self-organized integration vs. self-organized disintegration: an unfinished study - Portugali, Juval (Frontiers in Network Physiology, 2025)
This paper refers to an issue Haken and myself were discussing, started to work on, prepared a preliminary draft, but never managed to complete and transform it into a full-scale study and publication. Here, in memoriam of Hermann Haken, my dear friend and colleague for many years, I present it as it is – an unfinished study with some innovative ideas that will have to be further elaborated in the future.